Effects of MVA85A vaccine on tuberculosis challenge in animals: systematic review - Mcshane, H; Hatherill, M; Hanekom, W; Evans, T (Oxford University Press, 2016)
We write in response to the article by Kashangura et al. who conducted a systematic review of the animal efficacy data concerning MVA85A, a candidate TB vaccine.